Recycling at school: A case study in Monte Patria, Chile - Jaime Muñoz, Eduardo Antonio (2021)
Recycling is an environmental practice aimed at the reuse of solid waste that has completed a life cycle and that, due to the formation of microbasurales, requires to be reused in order to reduce the amount of waste in the environment. Considering the relevance of this theme, this article has been prepared that aims to know and describe this educational experience around recycling in the rural school of Chilecito, located in the municipality of Monte Patria, Region of Coquimbo, Chile. The study case is part of a project of the Ministry of Environment of the Government of Chile. The methodology used provided workshops with students and the use of educational materials. The results contemplate, the presentation of tables with information related to the pedagogical activities carried out by the students. In the discussion, the impressions of the students are presented, some assessments linked to recycling with the school curriculum and the apoderados manifest their impressions in relation to the theme.